Investigation on Characteristics of Pressure Drop for Binary Mixture in Horizontal Micro-fin Tube - 段雪涛; 马虎根; 邬志敏 (Zhileng xuebao)
Using non-azeotropic refrigerant mixture R32/R134a as the working fluid,the experimental study on the horizontal micro-fin tubes was conducted.Several factors affecting pressure drop were analyzed,and the characteristics of flow boiling and pressure drop of the mixture in the horizontal micro-fin tubes were discussed.Based on the experimental data,the acceleration resistance was calculated according to the phase separation model,and the empirical correlations for frictional resistance were obtained.The calculation result is well consistent with the experimental data.